(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The aim of the study is to investigate the erosion of degraded brown soils used mainly under grain crops in the Shamakhi region, south-east of the Greater Caucasus, and erosion of moderately eroded species to the soil fertility parameters